Pragmalinguistic Features of American Presidents' Inaugural Addresses of the Last Century (1913-2013) - Anna Gabets; Arnau Barios Gené (National Research University Higher School of Economics, 2016)
This paper studies the pragmalinguistic markers of the political discourse in American presidents' inaugural addresses made from 1913 to 2013 and concentrates on the language units that reveal the potential of perlocutionary speech acts. The study analyzes the role of such domains of pragmalinguistics as deixis, reference, presupposition, cognitive structures in inaugural addresses, and their representation in speeches. The method of discourse-analysis, the method of contextual analysis, and the method of quantitative processing are used in the study. The means of deixis have several functions in these speech texts, providing some extra-linguistic information and additional meaning for the utterances. Firstly, the change of deictic center conveys a certain shift of attention and redirects the addressee's thoughts. Secondly, the means of deixis represent presuppositions, ones which members of the public are unlikely to question since these presuppositions are explicitly referred to and the information provided includes people's background assumptions. Thirdly, personal, temporal and spatial deixes are integrated in the actualization of the most important concept found in every speech of every American president - the concept of the "American nation": deictic forms along with nouns with evaluative implications add to the pragmatic effect of the concept reflected in speech. Fourthly, the deictic means participate in the construction of a binary that juxtaposes "us" vs. "them", typical of political utterances in the genre of inaugural addresses. A special form of reference constituting an important part of the concept of the "American nation" in inauguration addresses is precedent phenomena. Their main sources are the Bible, speeches of former politicians, texts of famous American documents. Reference to religious discourse and parts of national history familiar to everyone brings the feeling of joy to the public appealing to a basic national myth of a happy community. Thus means of deixis, presupposition and special type of reference are the characteristic of American inauguration speeches used for the purposes of strong pragmalinguistic effect. The dynamics of the usage of the precedent phenomena and other constituent parts of the concept "American nation" reflects the changes in political context of the epoch.